Pengaruh Perfeksionisme Terhadap Kecemasan Ujian Siswa Sekolah Menengah Atas Negeri 1 Kabupaten Takalar - Koernia Jabbar; Ahmad Razak; Dian Novita Siswanti (CV. Ulil Albab Corp, 2022)
Individuals with perfectionism will feel anxious while facing the test. This research aims to examine how perfectionism has influence on the test anxiety of the 12th grade student at SMAN 1 Takalar. The research was conducted on students who had taken the Computer Based Written Test (UTBK) in 2020 and had tendency to perfectionism. Throughout cluster random sampling technique, the participants of this research were 107 people. The results showed that perfectionism had a significant effect on test anxiety, with a correlation coefficient of 0.085. The implication of this study is useful for schools to minimize the possibility of test anxiety by paying more attention to the tendency of maladaptive perfectionism in students.